Distribution of Iliac Artery Calcification on Unenhanced Computed Tomography Scans Performed on Potential Recipients Prior to Renal Transplantation. Issue 3 (August 2021) - Marcuzzi, Adrian; Wang, Stella; Tyrrell, Pascal N.; Ravichandran, Pradeep; Marcuzzi, Danny; Prabhudesai, Vikramaditya; Stewart, Robert
Purpose: To investigate whether a significant difference exists between the calcification of the common iliac arteries (CIAs) and the external iliac arteries (EIAs) and test for associations between clinical factors and the distribution of calcification. Methods: A retrospective review of renal transplant candidates who underwent a routine preoperative unenhanced computed tomography yielded 214 patients. Agatston scores for the patients' left CIA, left EIA, right CIA, and right EIA were assigned. A retrospective search of patient records screened for 5 clinical factors (diabetes, hypertension, coronary artery disease [CAD], smoking, and dialysis). Data were assessed using a 2-sided t test, odds ratio, and a multivariate linear regression calculated through generalized estimating equation (GEE). Results: The log-transformed Agatston scores in the CIA were found to be significantly greater than that in the EIA ( t = 9.57, P < .0001), with a mean difference of 1.5078 (95% confidence interval: 1.1962-1.8194), indicating relative EIA sparing. There were no significant differences in calcification between the right and left sides. Generalized estimating equation found that CAD and smoking demonstrated independent positive associations with EIA sparing (GEE = 2.6464 [ P = .0197] and 1.9092 [ P = .0470], respectively). Age was also significantly associated and indicated that EIA sparing remained relatively constant throughout patients' lives (GEE = 1.0711 [ P < .0001]). Conclusion: This study has demonstrated statistically significant EIA sparing in end-stage renal disease patients and identified CAD and smoking as associated factors. This phenomenon warrants further investigation into its biological mechanisms and the impact of EIA sparing on outcomes following transplants.